Putty Hill [videorecording (DVD)] ; Hamilton - Porterfield, Matt; Ray, Cody; Ray, Dustin; Ferreira, Sky, 1992- (Cinema Guild, 2011)
Putty Hill: A beautifully realized portrait of a close-knit community on the outskirts of Baltimore. At a neighborhood karaoke bar, friends and family gather to remember a young man who passed away. Knowing little about his final days, they attempt to reconstruct his life. In the process, they offer a window onto their own lives, an evocative picture of working-class America, dislocated from the progress and mobility around them, but united in pursuit of a shared dream.